Integrating Farmers’ Rights to Equitable Benefit Sharing Into the Malaysian Plant Variety Law: Learning from Others - Murshamshul Kamariah Musa; Abdul Majid Tahir Mohamed; Abdul Majid Hafiz Mohamed (Universitas Airlangga, 2019)
The Farmers’ Rights concept is part of an international treaty of which Malaysia is one of the signatory parties. The International Treaty on Plant Genetic Resources for Food and Agriculture (FAO Treaty 2004), articulated four core rights under the Farmers’ Rights concept – namely the right to traditional farming knowledge, the right to seed, the right to equitable benefit sharing and the right to participate in the decision-making process. Article 9.2 (b) of FAO Treaty 2004 stipulates that farmers should be given equal opportunity to equitably participate in sharing benefits from the use of plant genetic resources for food and agriculture. The right to equitable benefit sharing legally justifies among others, the rights of smallholder farmers who have been breeding seeds for generations to receive benefits; either monetary or non-monetary from any commercialization of the seeds that have been developed by them. Non-monetary benefits include access to seeds for their farm. This paper investigates to what extent the existing legal provisions of plant variety law in Malaysia has integrated this right to equitable benefit sharing to small farmers as compared to similar legislation in India and under African Union (AU Model Law for the Protection of the Rights of Local Communities, Farmers and Breeders, and for the Regulation of Access to Biological Resources). These two legal frameworks aimed to protect their small farming communities are cited as legislation with the best practices on implementing Farmers’ Rights core rights. The aim is for Malaysia to learn from these countries in order to ensure legal protection for small farmers’ right to equitable benefit sharing of their plant genetic resources.